Navigating the magnetic contribution of the commonly used single-crystal substrates SrTiO3 (100) and LaAlO3 (100) in weak magnetic thin films - Mandal,AK; Sarkar,S; Chandra,M; Mandal,S; Chowdhury,S; Jana,A; Bagri,A; Bera,AK; Kumar,D; Das,I; Rajhunathan,R; Phase,DM; et al. (Journal of Physics D Applied Physics, 2024)
In recent years, thin films of weak ferromagnetic materials have been in huge demand; however, probing their magnetic characteristics has been difficult due to contributions from underlying substrates. In the present study, we have analyzed the magnetic properties of the commonly used single-crystal SrTiO3 (100) and LaAlO3 (100) substrates and performed a time-dependent annealing protocol in vacuum and ambient oxygen pressure to mitigate the intrinsic weak ferromagnetic contributions from these substrates arising due to the presence of disorder or defects such as vacancies in the pristine substrates. It is shown that after proper air annealing, the substrate magnetic background becomes diamagnetic. When such air-annealed diamagnetic substrates are used for the deposition of low-thickness films carrying low magnetic moments such as SrRuO3 and SrMnO3 thin films, their magnetic transitions are explicitly observed. The proposed annealing protocols help to improve the signal from weak magnetic samples. This allows us to analyze the film’s magnetic properties without worrying about the contribution from the substrate.